The Prebisch-Singer Hypothesis: Four Centuries of Evidence - Harvey, David I; Kellard, Neil M; Madsen, Jakob B; Wohar, Mark E (The Review of Economics and Statistics, 2010)
We employ a unique data set and new time-series techniques to reexamine the existence of trends in relative primary commodity prices. The data set comprises 25 commodities and provides a new historical perspective, spanning the seventeenth to the twenty-first centuries. New tests for the trend function, robust to the order of integration of the series, are applied to the data. Results show that eleven price series present a significant and downward trend over all or some fraction of the sample period. In the very long run, a secular, deteriorating trend is a relevant phenomenon for a significant proportion of primary commodities.